Faktor-Faktor Operasional Sebagai Anteseden dari Kinerja Keberlanjutan pada Perusahaan Manufaktur - Dimas Aulia Kalimantoro; Wahyuningsih Santosa; Triwulandari SD (Institut Transportasi dan Logistik Trisakti, 2023)
This study aims to analyze the effect of Total Quality Management, Total Productive Maintenance, Innovation Capability, Circular Economy, and Industry 4.0 on sustainability performance. Sustainability performance in this study is focused on implementing corporate sustainability in the economic, social, and environmental sectors. The data used in this research is primary data, which is data obtained directly from the field, which is the object of research. The research sample was selected using a purposive sampling method in order to obtain 10 companies engaged in the manufacturing industry located in DKI Jakarta with a total of 203 respondents. This study uses cross-sectional time, where data is collected only once for one month. The data analysis used in this study uses Structural Equation Modeling data processing, which is used to examine and justify a hypothesis that has been tested in previous studies. The results of the study show that total quality management, innovation capability, and industry 4.0 have a positive and significant effect on sustainability performance. Meanwhile, for the circular economy, it has a negative and significant effect on sustainability performance, while for total productive maintenance, it has no effect on sustainability performance in manufacturing industry companies in DKI Jakarta.